Headquarters Control and Its Legitimation in a Chinese Multinational Corporation: The Case of Huawei. (December 2021) - Hong, Jacky F. L.; Snell, Robin Stanley
ABSTRACT: Based on interviews and documentary analysis, we analyzed the mechanisms being adopted by the HQ of Huawei, a Chinese MNC, for controlling the outputs and processes of its foreign subsidiaries and social behaviours within them and how these controls were supported by corresponding strategies of legitimation. The controls comprise key performance indicators, standard operating procedures, divided subsidiary mandates, HQ-centric rotational expatriation, military-style induction, public oath-taking and self-criticism ceremonies, and training in and role-modelling of core values. The HQ provides comprehensive legitimation for each of these control mechanisms, drawing on five strategies of legitimation, which comprise espousals of organizational benefits, inducement, affirmation, moral exhortation, and narrativization. In many cases, the legitimizing statements have been provided by Mr. Ren, Huawei's founder and CEO, whose authority appears to have been important in conferring legitimacy to the HQ. The historical path of Huawei's development as an MNC has also been salient in conferring legitimacy to the HQ. Our findings suggest that interviewees regard the controls as legitimate, that the subsidiaries broadly comply with the controls, and that micro-political contestation is largely absent. 摘要: 通过面谈和文件分析，我们研究华为作为中国的跨国企业，如何通过制定合法性策略支持总部全面控制海外子公司的产出、过程和社会行为。总部的控制机制包括关键表现指标、标准运作程序、分摊子公司授权、以总部为核心的外派员轮转、军事化归纳、公众宣誓、自我批评仪式和具有企业核心价值的好榜样培训。为了给每种控制机制全面的合法性，总部采用了五种不同的策略，其中包括组织利益的奉献、诱导、肯定、道德劝诫和陈述。很多合法性陈述都是由华为的创辨人任正飞所提供，因为他的权威能授予总部很大程度的合法化去控制子公司。除此以外，华为作为一家跨国企业的过往发展历程也给予总部很多的帮助。我们的硏究结果表明，受访者觉得总部的控制机制具有高度合法性，子公司能广泛地遵守总部的各种控制要求，而子公司内的政治争议一般都不存在。 АННОТАЦИЯ: На основе целого ряда интервью и анализа документов, мы проанализировали механизмы, которые применяются в штаб-квартире Huawei, китайской многонациональной корпорации, для контроля результатов, процессов и социального поведения в зарубежных дочерних компаниях, а также то, как этот контроль поддерживается соответствующими стратегиями легитимации. Способы контроля включают в себя ключевые показатели эффективности, стандартные рабочие процедуры, разделение полномочий между филиалами, ротационную экспатриацию в штаб-квартире, вводный инструктаж военного образца, публичные церемонии присяги и самокритики, а также обучение и ролевое моделирование основных ценностей. Штаб-квартира обеспечивает всестороннюю легитимацию каждого из этих механизмов контроля, опираясь на пять стратегий легитимации, а именно предоставление организационных преимуществ, мотивацию, одобрение, моральное наставление и нарративизацию. Во многих случаях заявления, обеспечивающие легитимность, были предоставлены господином Реном, основателем и генеральным директором Huawei, авторитет которого, по всей видимости, является важным для придания легитимности штаб-квартире. Исторический путь развития Huawei как многонациональной корпорации также играет важную роль в придании легитимности штаб-квартире. Наши результаты показывают, что респонденты считают меры контроля легитимными, что дочерние компании в основном подчиняются контролю и что недовольство на микроуровне в общем отсутствует. RESUMEN: Con base en entrevistas y análisis documental, analizamos los mecanismos que han sido adoptados por la casa matriz de Huawei, una empresa multinacional china, para controlar los resultados y los procesos de sus filiales extranjeras y los comportamientos sociales dentro de estas, y como estos controles se apoyan en las correspondientes estrategias de legitimación. Los controles comprenden indicadores de desempeño clave, procedimientos operativos estándar, mandatos divididos de las filiales, expatriación rotativa centrada en la casa matriz, inducción de estilo militar, ceremonias públicas de juramento y ceremonias de autocrítica, juego de roles y capacitación en valores clave. La casa matriz suministra una legitimación amplia para cada uno de esos mecanismos de control, recurriendo a cinco estrategias de legitimación, las cuales comprende la adhesión a los beneficios organizacionales, alicientes, afirmación, exhortación moral, y narrativización. En muchos casos, las declaraciones de legitimización que ha sido proporcionadas por el Sr Ren, el fundador y CEO de Huawei, cuya autoridad parece haber sido importante para conferir legitimidad a la casa matriz. La trayectoria histórica del desarrollo de Huawei como empresa multinacional también ha sido importante para conferir legitimidad a la casa matriz. Nuestros hallazgos sugieren que los entrevistados consideran que los controles son legítimos, que las filiales acatan ampliamente los controles, y que la refutación micro-política es en gran medida ausente.